(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
This article focuses on team performance as well as player performance prediction, with team performance being evaluated using a variety of machine learning algorithms and web scraping methodologies. Data is refined and modified efficiently to get the desired accurate results. Advanced Statistics is used to get results. The prediction includes final league table of teams, whether a team is going to have a better season than the previous one. Prediction is also done to evaluate the rating of a defender.